2016
DOI: 10.4067/s0718-19572016000200026
|View full text |Cite
|
Sign up to set email alerts
|

Colouration patterns of two species of the genus Scartichthys (Blenniidae: Perciformes) in the coastal area of northern Chile

Abstract: Abstract.-The aim of this study was to report the colouration patterns of live specimens of two Blenniidae species: Scartichthys gigas and S. viridis, from tide pools in the coastal area of 3 localities of northern Chile. Colouration patterns for S. gigas were: the two-bar front head covered/uncovered and the uniform orange-brown, found in specimens associated to kelps, for juveniles; an intermediate juvenile-adult reticulated bar-stained pattern described for the first time and the reticulated pattern for adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 2 publications
0
16
0
Order By: Relevance
“…Scartichthys viridis/gigas and Pinguipes chilensis were the most abundant species at all study sites, being more frequent on barren grounds albeit with small differences in horizontal videos (wider field of view). Scartichthys viridis/gigas are comparatively small fishes (10–20 cm adult size) that are not commercially fished (Méndez-Abarca & Mundaca, 2016) and are very common in subtidal habitats of northern Chile (Villegas et al, 2018; this study). On the other hand, Pinguipes chilensis was consistently present on barren grounds but not in kelp forests, which appears to be typical for this species, since previous studies had observed that its abundances increase when density of kelp forests decreases (Pérez-Matus et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scartichthys viridis/gigas and Pinguipes chilensis were the most abundant species at all study sites, being more frequent on barren grounds albeit with small differences in horizontal videos (wider field of view). Scartichthys viridis/gigas are comparatively small fishes (10–20 cm adult size) that are not commercially fished (Méndez-Abarca & Mundaca, 2016) and are very common in subtidal habitats of northern Chile (Villegas et al, 2018; this study). On the other hand, Pinguipes chilensis was consistently present on barren grounds but not in kelp forests, which appears to be typical for this species, since previous studies had observed that its abundances increase when density of kelp forests decreases (Pérez-Matus et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…All fishes were identified to species based on their shape, colour, and swimming habits, with the exception of Scartichthys , of which two species occur in the study area, Scartichthys viridis and Scartichthys gigas . These species are common in northern Chile and display variable colour patterns (Méndez-Abarca & Mundaca, 2016), making it sometimes difficult to distinguish among them, especially in videos with limited visibility. As both species are of similar size and ecological habits, we treated them as Scartichthys viridis/gigas (see also Villegas et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Counts of incisor teeth and dorsal fin rays followed Williams (1990) and were taken using a Leica model EZ4 binocular. Following Williams (1990) and Mndez-Abarca & Mundaca (2016), specimens were photographed using digital cameras (Nikon D90 and Canon EOS T5) upon collection or in the laboratory to identify their fresh colouration patterns. The total counts of dentary incisors (DI) are diagnostic for only two of the four species of this genus (S. gigas and S. variolatus).…”
Section: Morphological Analysesmentioning
confidence: 99%
“…Interestingly, Scartichthys are considered as blenniid giants as adults can be up to 300 mm in length. Additionally, they are known among local fishermen as borrachillas [drunk] because the consumption of the flesh of these fish leads to a sleepy or drunk feeling (Williams, 1990;Mndez-Abarca & Mundaca, 2016). Despite these interesting aspects of their ecology, Scartichthys blenniids remain difficult (Prez-Matus et al, 2007;Riquelme-Prez et al, 2019) or even impossible to identify at the species level in the field (Villegas et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation